Spanish verbs made simple(r) - Brodsky, David, 1950- (University of Texas Press, 2005)
"Provides rules for conjugating all classes of Spanish verbs, including irregular verbs. Includes discussion of the uses of the subjunctive and the difference between the verbs ser and estar"--Provided by publisher.